Post-COVID Era Teaching: Analysis on Students Perception of Preferred Learning Activities and Satisfaction in English for Pharmacy - Ika Sulis Setianingsih (Journal on Education, 2024)
English proficiency is a vital skill for pharmacy students, encompassing medical terminology, patient communication, and academic writing essential for their future professional endeavours. This study aimed to evaluate the post-COVID English for Pharmacy fully offline theory classes by investigating students' perception of preferred learning activities and their satisfaction levels in learning English for Pharmacy during the post-COVID era. This study evaluated two meetings of theory related to Explaining Something in English and Explaining about Prescriptions in English. This study employed a cross-sectional survey which focused on the descriptive description on the preferred learning activities and satisfaction in English for Pharmacy. The subject of this study were students of Diploma 3 Pharmacy Department in the academic year of 2023/2024. The sample of this study were 58 students. The findings showed that speaking was the preferred skill for the topic, and conversation practice became the most preferred activity for the topic, students were satisfied with the instructor role, and had a positive attitude toward the topic and the course. Further investigations which can complete the whole picture toward the topic have to be done, especially in seeking the relationship among students’ satisfaction, perception, and the learning outcome for this course.